Pengaruh Sholat Dhuha dan Bacaan Dzikir terhadap Spiritual Quotient Siswa di MTs N 6 Agam Kubang Putih - Nofembra Putri; Charles; Salmiwati; Afrinaldi (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
In this study, the author uses a quantitative approach with a correlation research type. The data analysis technique uses simple linear regression and multiple linear regression. The sampling technique in this study uses Probability Sampling with a sample size of 257 from a population of 778. The model chosen is simple random sampling, the data collection technique uses a questionnaire, then analyzed using the Anova test with the help of SPSS 2020. The findings from the research day are as follows: 1) Based on the results (tcount> ttable) with a tcount value of 14.357 and a ttable of 1.9693. The effect of dhuha prayer on students' spiritual quotient at MTsN 6 Agam Kubang Putih is 47.7%. 2) Based on the results (tcount>ttable) with a tcount value of 12.789 and a ttable of 1.9693. The effect of dhikr on students' spiritual quotient at MTsN 6 Agam Kubang Putih is 39.7%. 3) Based on the results (Fcount>Ftable) with an Fcount value of 125.789 and an Ftable of 3.04. At a 5% error level with a significance level of 0.000 < 0.05, the Dhuha prayer and dhikr together have an effect on the spiritual quotient of students at MTsN 6 Agam Kubang Putih by 49.4%.